Efecto de la temperatura y la irradiancia sobre el crecimiento, la propagación vegetativa y la actividad fotosintética del alga invasora Rugulopteryx okamurae (Dictyotales, Ochrophyta). - Rosas-Guerrero, Jesús; Carmona-Fernández, Raquel; Altamirano-Jeschke, María (CEIMAR, 2021)
The invasive algae Rugulopteryx okamurae (Dictyotales, Ochrophyta) is producing recently important blooms in southern Spain, affecting biodiversity, fishing industry and tourism. For this reason, it is essential to identify the factors that determine the high invasiveness. In this context, the objective of this study focuses on determining the effect of temperature and irradiance on growth, vegetative propagation and photosynthetic activity of R. okamurae. Apical and interdichotomous fragments of thallus were cultivated under different temperatures (14 and 22 °C) and irradiances (35 and 70 µmol photons m-2 s-1) under controlled laboratory conditions. The effects of these treatments were studied on the relative growth rate, propagules proliferation and the photosynthetic activity expressed as fluorescence of chlorophyll a. Results show that the growth capacity of the thallus depends on the presence or not of the apical cells in the thallus, and that their presence, determines the potential of the thallus for vegetative propagation. Moreover, it has been observed that conditions of low temperature and irradiance favour the propagation capacity of the species, as well as its photosynthetic activity. These results are of great interest to understand the invasive behaviour of the species, since they allow us to identify, on the one hand, the breakdown of thallus as a propagation mechanism of the species that favours the recruitment of new clone individuals, and, on the other hand, to determine that this capacity is active in the annual thermal range of the invaded region.
Ayuda Plan propio de Investigación de la Universidad de Málaga. Proyecto Rugulopteryx. Fundación Biodiversidad. MITECO.
Keywords: Eficiencia fotosintética; Esfuerzo reproductor; Estrecho de Gibraltar; Propágulo; Tasa de crecimiento